Krzywdzenie a przyzwalanie na krzywdę. Część II: Prawo do samoobrony - Mirosław Rutkowski (Analiza i Egzystencja, 2019)
Hurting and allowing harm. Part II: A right to self defense In this article I defence the thesis that there is a morally significant difference between doing harm (or harming) and merely allowing harm to happen.